1991
DOI: 10.1007/bf02402964
|View full text |Cite
|
Sign up to set email alerts
|

Plasma surface modification of advanced organic fibres

Abstract: A marked improvement in the interlaminar shear strength and flexural strength of aramid/ epoxy composites is observed when the fibres are pretreated in an ammonia or ammonia/ nitrogen gaseous discharge (plasma) to introduce amine groups on to the fibre surface. Scanning electron and optical microscopic observations are used to examine the microscopic basis for these results. Scanning electron micrographs of shear fracture surfaces show clean fibre/matrix separation in composites made from untreated fibres, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Biswas et al [9] observed an increase in the roughness of para-aramid fibers with time of activation at atmospheric pressure plasma (4 kW, 30 s, 1 min, 2 min, 3 min). Brown et al [23], by treating the para-aramid fabric with NH 3 plasma (100 W from 0.25-20 min) observed an increase in surface fibrillation. Chen et al [24] investigated the effect of atmospheric pressure plasma (720 W) on surface topography changes of para-aramid 3D fabric subsequent layers.…”
Section: Sem/eds Analysismentioning
confidence: 98%
“…Biswas et al [9] observed an increase in the roughness of para-aramid fibers with time of activation at atmospheric pressure plasma (4 kW, 30 s, 1 min, 2 min, 3 min). Brown et al [23], by treating the para-aramid fabric with NH 3 plasma (100 W from 0.25-20 min) observed an increase in surface fibrillation. Chen et al [24] investigated the effect of atmospheric pressure plasma (720 W) on surface topography changes of para-aramid 3D fabric subsequent layers.…”
Section: Sem/eds Analysismentioning
confidence: 98%
“…More widely used methods aim at the functionalization of the fiber surface. For AF and CF acidic oxidation , fluorination , and plasma treatment are described. For CF also ozone treatment or electrochemical oxidation are used.…”
Section: Fiber/matrix Interactionmentioning
confidence: 99%
“…However, the interfacial strength is too weak to raise total performance of the composite, though some surface modification methods have been proposed, including plasma treatment [1,2] and chemical modification [3,4]. These modification methods cause the fibrillation of fiber and result in the reduction of fiber strength.…”
Section: Introductionmentioning
confidence: 99%